REKAYASA PERANGKAT LUNAK UNTUK PENJUALAN PERLENGKAPAN PENGANTIN ADAT MINANGKABAU BERBASIS WEB - Indra Warman, S.Kom,. M.Kom (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2013)
Pasar Raya Padang is a trading business that provides a variety of Minangkabau’s wedding supplies and have many customers from various regions in the province of West Sumatra and off western Sumatera. Within a month, the number of buyers at the Syaf store bridal supplies more than 100 people. Meanwhile, in a terms of customer service, recording and processing of data items and sales reports are still using manual systems. In this research,the renewalof theold system tothe newsystem by making the Software Engineering for Minangkabau’s Traditional Bridal Supplies Sales Web-based programming language by using php and mysql 5.1.33 database. This study aims to develop an information system that can simplify Syaf shopkeepers to process data relating to the sale of Minangkabau’s Traditional wedding supplies. With the web-based sales system, it is capable for serving the needs of the customers to make a transaction in order to save time without having consumers come to the store. Meanwhile, side Syaf stores can sell goods online sale’s and manage sale’s data processing. In addition, Syaf Store’s website is equipped with charts and sales reports to facilitate Syaf Store to make a decisions fast and accurate.